Non-small cell lung cancer in stages I-IIIB - Wurstbauer, Karl; Weise, Hannes; Deutschmann, Heinz; Kopp, Peter; Merz, Florian; Studnicka, Michael; Nairz, Olaf; Sedlmayer, Felix (Strahlentherapie und Onkologie, 2010)
To investigate therapeutic outcome of dose escalation ≥ 80 Gy in nonresected non-small cell lung cancer (NSCLC).
Gesehen am 22.05.2024